Analysis of Morphological Change during a Co-invading Assemblage of Lizards in the Hawaiian Islands - John G. Phillips; Travis J. Hagey; Molly Hagemann; Eben Gering (Evolutionary Biology, 2024)
Phenotypic change plays diverse roles in species’ colonization, but most invasion studies target single species. To compare ecomorphological changes among co-invading species with overlapping niches, we examined three lizards on the island of O‘ahu ( Anolis carolinensis, A. sagrei, Phelsuma laticauda ). Using specimens from three decades of unfolding invasions obtained through museum collections and contemporary field work, we quantified shifts in three traits: snout vent length (SVL), forelimb-, and hindlimb-length (limb lengths relative to SVL). We hypothesized that competition among these three species has led to ecological shifts that will be detectable through morphological change. Overall, we found that unique patterns of phenotypic change were both species-specific and sex-specific within species: (1) male A. sagrei , female A. carolinensis , and male P. laticauda increased in SVL and (2) relative hindlimb length increased in female A. carolinensis since the 1980s. The observed changes involve traits that may be consequential to invasion dynamics. This study illustrates how museum- and field-based research can be integrated to document nuanced temporal patterns in the phenotypes of co-invading species that share similar niches in native ranges, raising questions about the underlying process(es) driving species- and sex-specific change in co-invaded systems.

Untangling the cecal microbiota of feral chickens by culturomic and metagenomic analyses - Chiara Ferrario; Giulia Alessandri; Leonardo Mancabelli; Eben Gering; Marta Mangifesta; Christian Milani; Gabriele Andrea Lugli; Alice Viappiani; Sabrina Duranti; Francesca Turroni; Maria Cristina Ossiprandi; Ricardo Hiyashi; et al. (Environmental Microbiology, 2017)
Summary Different factors may modulate the gut microbiota of animals. In any particular environment, diet, genetic factors and human influences can shape the bacterial communities residing in the gastrointestinal tract. Metagenomic approaches have significantly expanded our knowledge on microbiota dynamics inside hosts, yet cultivation and isolation of bacterial members of these complex ecosystems may still be necessary to fully understand interactions between bacterial communities and their host. A dual approach, involving culture‐independent and ‐dependent techniques, was used here to decipher the microbiota communities that inhabit the gastro intestinal tract of free‐range, broiler and feral chickens. In silico analysis revealed the presence of a core microbiota that is typical of those animals that live in different geographical areas and that have limited contact with humans. Anthropic influences guide the metabolic potential and the presence of antibiotic resistance genes of these different bacterial communities. Culturomics attempts, based on different cultivation conditions, were applied to reconstruct in vitro the microbiota of feral chickens. A unique strain collection representing members of the four major phyla of the poultry microbiota was assembled, including bacterial strains that are not typically retrieved from the chicken gut.

Male treefrogs in low condition resume signaling faster following simulated predator attack - Michael C. Kuczynski; Levi Storks; Eben Gering; Thomas Getty (Behavioral Ecology and Sociobiology, 2016)

All the better to see you with: a review of odonate color vision with transcriptomic insight into the odonate eye - Seth M. Bybee; K. Kaihileipihamekeola Johnson; Eben J. Gering; Michael F. Whiting; Keith A. Crandall (Organisms Diversity & Evolution, 2012)

Prevalence and differential host‐specificity of two avian blood parasite genera in the Australo‐Papuan region - JON S. BEADELL; EBEN GERING; JEREMY AUSTIN; JOHN P. DUMBACHER; MIKE A. PEIRCE; THANE K. PRATT; CARTER T. ATKINSON; ROBERT C. FLEISCHER (Molecular Ecology, 2004)
The degree to which widespread avian blood parasites in the genera Plasmodium and Haemoproteus pose a threat to novel hosts depends in part on the degree to which they are constrained to a particular host or host family. We examined the host distribution and host‐specificity of these parasites in birds from two relatively understudied and isolated locations: Australia and Papua New Guinea. Using polymerase chain reaction (PCR), we detected infection in 69 of 105 species, representing 44% of individuals surveyed ( n = 428). Across host families, prevalence of Haemoproteus ranged from 13% (Acanthizidae) to 56% (Petroicidae) while prevalence of Plasmodium ranged from 3% (Petroicidae) to 47% (Ptilonorhynchidae). We recovered 78 unique mitochondrial lineages from 155 sequences. Related lineages of Haemoproteus were more likely to derive from the same host family than predicted by chance at shallow (average LogDet genetic distance = 0, n = 12, P = 0.001) and greater depths (average distance = 0.014, n = 11, P Haemoproteus subclades identified in a maximum likelihood phylogeny, host‐specificity was evident up to parasite genetic distances of 0.029 and 0.007 based on logistic regression. We found no significant host relationship among lineages of Plasmodium by any method of analysis. These results support previous evidence of strong host‐family specificity in Haemoproteus and suggest that lineages of Plasmodium are more likely to form evolutionarily–stable associations with novel hosts.